Vocabulary Test Design For The First Year Student Of SLTP Muhammadiyah 2 Surakarta - Sumiyatun, Sumiyatun (2006)
This study is aimed at describing vocabulary test design for the first year student of SLTP Muhammadiyah 2 Surakarta. The vocabulary test design for the first year student of SLTP Muhammadiyah 2 Surakarta covers the goal, materials, kinds, form and tehnique of the test. The objectives of this research are to describe: 1) the vocabulary test design, 2) the difficulties faced by student and teacher in vocabulary test, 3) the advantages of the vocabulary test. In this research the writer carried out observation and interview the English teacher. Technique for analyzing data are: 1) describing all the data obtained from observation and interview, 2) interpreting the analyzed data, 3) classifying the difficulties faced by the teacher and the student in the vocabulary test, and 4) describing the type of vocabulary test design. There are the goals of the vocabulary test 1) To know the progress of the teaching-learning process, 2) To know the students ability. Kinds of the test can be classified into the placement test, the formative test, the diagnostic test and the summative test. The technique of the test teacher used an oral test that given in individual test or group test. The result of research shows that there are the advantages and disadvantages of daily oral test. The advantages are students become active, diligent and more concern in teaching learning process. The disadvantages are the teacher needs a good preparation so the students do not fear and nervous when they face the test.